CONTEMPORARY RESEARCH TRENDS IN HUMAN-COMPUTER INTERFACE DESIGN - ZHOU , T.; YEZHOVA, O. (Art and Design, 2024)
Objective: analyzing the current status and developmental trends in the field of interface design, and to establish a classification framework for the characteristics and requirements of various application domains in interface design Methodology. Using the methods of quantitative analysis, literature review, and information visualization techniques with Citespace software to visualize the relevant literature information in the field of interface design. The creation of scientific knowledge maps depict the structure and distribution of scientific knowledge, enabling a comprehensive analysis of the field of interface design from multiple perspectives and levels. Results. This paper presents the development trend of interface design research in Scopus database from 2015 to 2023 in the form of visual knowledge graph. Through literature analysis, the current research focus and future research direction of interface design are obtained. At the same time, ten main application carriers of interface design are listed, their characteristics are analyzed from the perspective of interface design, and corresponding design suggestions are given. Scientific novelty. For the first time, the literature research knowledge map of interface design was summarized by combining Citespace visualization software. The categories and key points of interface design research were presented through visualization maps. At the same time, the main application scenarios and categories of interface design were summarized, thus providing a theoretical basis and reference database for interface design. Practical significance. The study is recommended for practical implementation in the field of interface design.